Sanctioning value: The legal system, hyper-power and the legitimation of MP3. (June 2017) - Denegri-Knott, Janice; Tadajewski, Mark
This article offers an historical account of the contestation surrounding MP3 and its legitimation as a consumer choice option. We juxtapose our narrative against the service-dominant logic (SDL) literature, which positions the consumer as the co-creator of value. In these debates issues of power and politics are downplayed. By contrast, we foreground the politicized processes that frame consumer choice options. Through a study of the legal disputes around MP3 and digital delivery services, we make a case that law courts provide the scaffolding for judgements of value in the market system. Contrary to proponents of SDL, value is not only a function of co-production between company and customer. Nor do all consumption practices acquire sufficient legitimacy to enter into legally sanctioned value co-creation interactions. This is a function of the 'hyper-power' practiced by the legal community and related actors, which constitute or deny value to product offerings. Value is not, therefore, necessarily phenomenologically determined by the ultimate consumer. Neither are they the sovereign individual of marketing lore. Their subjectivity is patterned by macro and meso actors and service provision is permitted when it is capable of enrolment within the circuits of capital accumulation.